EMPLOYMENT OF THE RURAL POPULATION IN SERBIA - Božić, Dragica (Economics of Agriculture, 2011)
Low employment, unfavourable employment structure and high unemployment rates are known to be the major disadvantages of the labour market in the rural regions of Serbia. Employment of the rural population characterizes low diversification of the rural economy, namely only 44.5% of those employed were found to be involved in agriculture. Accordingly, of the rural population employed most of them were registered in the processing industry (14.8%), wholesale and retail (10.5%) and civil engineering (4.4%). The high share of the employed rural population in agriculture was followed by its substantially low share in the total household income (6.8%). This points to low profitability in agriculture. The employed rural population in Serbia was found to be characterized by an unfavourable age and education structure. This was partly due to the demographic and eduction structure of the household members predominating in the employed rural labour. One of the properties of the employed rural population was the higher informal employment rate, especially of the female population.